2017
DOI: 10.4037/ccn2017940
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Versus Intermittent Subglottic Secretion Drainage to Prevent Ventilator-Associated Pneumonia: A Systematic Review

Abstract: Background Ventilator-associated pneumonia is associated with high morbidity and mortality in patients receiving mechanical ventilation. Subglottic secretion drainage, which may be performed continuously or intermittently, is believed to be an effective strategy for coping with ventilator-assisted pneumonia. Whether continuous or intermittent subglottic secretion drainage is superior for preventing ventilatorassisted pneumonia remains unknown. Methods This study is a comprehensive, systematic meta-analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Moreover, these VAP bundles and/or co-interventions were different in the included studies, potentially representing a source of heterogeneity. Sixth, although a subgroup analysis by SSD techniques could be feasible in this meta-analysis, it was disregarded because recent meta-analyses [25,62] did not report any differences between continuous and intermittent SSD to prevent VAP. Finally, due to the nature of the intervention, it could not be blinded for health staff, so only some RCTs were partially blinded.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these VAP bundles and/or co-interventions were different in the included studies, potentially representing a source of heterogeneity. Sixth, although a subgroup analysis by SSD techniques could be feasible in this meta-analysis, it was disregarded because recent meta-analyses [25,62] did not report any differences between continuous and intermittent SSD to prevent VAP. Finally, due to the nature of the intervention, it could not be blinded for health staff, so only some RCTs were partially blinded.…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria can migrate down the respiratory tract, increase the chance of pulmonary infections. Previous studies [ 43 , 44 ] have confirmed that the subglottic secretion drainage is beneficial to combating the pulmonary infection. Study [ 45 ] has shown that pulmonary infections are prone to occur after mechanical ventilation, mainly because the bacteria that adhere to the upper respiratory tract and it can be blown to the lower respiratory tract by tracheal tube.…”
Section: Discussionmentioning
confidence: 88%
“…It has been reported that the entry of bacteria into the lower respiratory tract by microaspiration of contaminated oropharyngeal and gastric secretions may be accountable for the occurrence of VAP (Blot et al, 2014). Therefore, many interventions have been used to prevent this process, such as the subglottic secretion drainage (SSD) (Muscedere et al, 2011;Wen et al, 2017), the administration of probiotics (Siempos et al, 2010) and oral hygiene care (Hua et al, 2016).…”
Section: Introductionmentioning
confidence: 99%